Laundry composition
By introducing carbonaceous materials and water-soluble carriers, especially graphene, into the solid fabric conditioner, the problem of easy rupture of solid fabric conditioner before use is solved, and the strength and stability are improved to form an easy-to-use concentrated composition.
Patent Information
- Application Number
- CN202380085107.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-14
- Filing Date
- 2023-12-08
- Publication Date
- 2025-07-18
AI Technical Summary
Existing solid fabric conditioners are prone to rupture before use, resulting in insufficient strength.
Carbonaceous materials, especially materials with 2D carbon lattice nanostructures such as graphene or derivatives thereof, are combined with quaternary ammonium compounds and water-soluble carriers to form solid fabric conditioning compositions, and tablets or sheets with enhanced strength are prepared by casting and evaporating water.
The strength and stability of the solid fabric conditioner is significantly improved, preventing breakage before use, and providing an easy-to-use concentrated composition form.
Smart Images

Figure BDA0005443676660000031 
Figure BDA0005443676660000032 
Figure BDA0005443676660000041
Abstract
Description
Technical Field
[0001] The present invention relates to solid fabric conditioning compositions. Background Art
[0002] Solid fabric conditioners provide consumers with a convenient and concentrated fabric conditioning composition. These compositions offer various benefits, including the ability to contain high levels of active ingredients and having a very low water content, resulting in easier storage and transportation.
[0003] Solid fabric conditioners come in different shapes and sizes, such as tablets, sheets, molded articles, etc. The strength of the fabric conditioner is important to prevent breakage before use. Summary of the Invention
[0004] It has been found that adding carbonaceous materials to solid fabric conditioners improves the strength of the solid composition.
[0005] Accordingly, a first aspect of the present invention provides a solid fabric conditioning composition comprising:
[0006] a 5 - 80 wt% of a fabric softening active containing a quaternary ammonium compound;
[0007] b a carbonaceous material; and
[0008] c a water-soluble carrier;
[0009] wherein the carbonaceous material has a 2D carbon lattice nanostructure.
[0010] The present invention also relates to a method for preparing a solid fabric conditioning composition, the method comprising the steps of:
[0011] a preparing a premix of the water-soluble carrier and water;
[0012] b adding the fabric softening active, the carbonaceous material and any remaining ingredients to the premix;
[0013] c casting the mixture onto a surface or into a mold; and
[0014] d removing the water, preferably by evaporation. Detailed Description of the Invention
[0016] These and other aspects, features, and advantages will become apparent to those of ordinary skill in the art upon reading the following detailed description and the appended claims. For the avoidance of doubt, any feature of one aspect of the invention can be used in any other aspect of the invention. The word "comprising" is intended to mean "including" but not necessarily "consisting of" or "constituted by". In other words, the listed steps or options need not be exhaustive. It should be noted that the embodiments given in the following description are intended to illustrate the invention and are not intended to limit the invention to those embodiments themselves. Similarly, unless otherwise stated, all percentages are weight / weight percentages. Unless in the operating examples and comparative examples, or otherwise expressly indicated, all numbers in this specification indicating amounts of materials or reaction conditions, physical properties and / or uses of materials should be understood to be modified by the word "about". A numerical range expressed in the form "from x to y" should be understood to include x and y. When multiple preferred ranges are described for a particular feature in the format from x to y, it should be understood that all ranges combining different endpoints are also covered.
[0017] The introduction level of all ingredients is in weight % of the final solid fabric conditioner product.
[0018] Fabric softening active
[0019] The compositions described herein contain a fabric softening active. The fabric softening active includes quaternary ammonium compounds.
[0020] The quaternary ammonium compound (QAC) preferably contains at least one chain derived from a fatty acid, more preferably at least two chains derived from a fatty acid. Generally, a fatty acid is defined as an aliphatic monocarboxylic acid having a chain of 4 to 28 carbons. The fatty acid can be derived from various sources, such as animal fats or plant sources. Preferably, the fatty acid chain is derived from plants. Preferably, the fatty acid chain of the QAC contains 10 - 50 wt% saturated C18 chains and 5 - 40 wt% monounsaturated C18 chains based on the weight of the total fatty acid chain. In another preferred embodiment, the fatty acid chain of the QAC contains 20 - 40 wt%, preferably 25 - 35 wt% saturated C18 chains and 10 - 35 wt%, preferably 15 - 30 wt% monounsaturated C18 chains based on the weight of the total fatty acid chain.
[0021] A preferred quaternary ammonium fabric softening active for the compositions described herein is the so-called "ester quat" or ester-linked quaternary ammonium compound.
[0022] Particularly preferred materials are ester-linked triethanolamine (TEA) quaternary ammonium compounds, which comprise a mixture of monoester, diester, and triester-linked components. Generally, TEA-based fabric softening compounds comprise a mixture of the monoester, diester, and triester forms of the compound, wherein the diester-linked component comprises no more than 70 wt%, preferably no more than 60 wt%, such as no more than 55%, or even no more than 45% of the fabric softening compound, and at least 10 wt% of the monoester-linked component.
[0023] A first group of quaternary ammonium compounds (QAC) suitable for use in the compositions is represented by formula (I):
[0024]
[0025] where each R is independently selected from C5 to C35 alkyl or alkenyl; R 1 represents C1 to C4 alkyl, C2 to C4 alkenyl, or C1 to C4 hydroxyalkyl; T can be O-CO (i.e., an ester group bonded to R through its carbon atom), or alternatively can be CO-O (i.e., an ester group bonded to R through its oxygen atom); n is a number selected from 1 to 4; m is a number selected from 1, 2, or 3; and X− is an anionic counterion, such as a halide ion or an alkyl sulfate, for example chloride ion or methyl sulfate. The diester variant of formula I (i.e., m = 2) is preferred and generally has monoester and triester analogs associated therewith. Such materials are particularly suitable for the compositions described herein.
[0026] A second group of QAC suitable for use in the compositions described herein is represented by formula (II):
[0027]
[0028] where each R 1 group is independently selected from C1 to C4 alkyl, hydroxyalkyl, or C2 to C4 alkenyl; and where each R 2 group is independently selected from C8 to C28 alkyl or alkenyl; and where n, T, and X− are as defined above.
[0029] Preferred materials of this second group include 1,2-bis[butyryloxy]-3-trimethylammonium chloride, 1,2-bis[hydrogenated butyryloxy]-3-trimethylammonium chloride, 1,2-bis[oleyloxy]-3-trimethylammonium chloride, and 1,2-bis[stearyloxy]-3-trimethylammonium chloride. Such materials are described in US4,137,180 (Lever Brothers). Preferably, these materials also contain a certain amount of the corresponding monoester.
[0030] A third group of QAC suitable for use in the compositions is represented by formula (III):
[0031] (R 1 )2-N * -[(CH2) n -T-R 2 2X - (III)
[0032] wherein each R 1 group is independently selected from C1-C4 alkyl or C2-C4 alkenyl; and wherein each R 2 group is independently selected from C8-C28 alkyl or alkenyl; and n, T and X- are as defined above. Preferred materials for this third group include bis(2-tallowoyloxyethyl)dimethylammonium chloride, its partially hardened and its hardened forms.
[0033] Specific examples of the fourth group of QACs are represented by formula (IV):
[0034]
[0035] A fifth group of QACs suitable for use in the composition is represented by formula (V)
[0036]
[0037] R1 and R2 are independently selected from C10-C22 alkyl or alkenyl, preferably C14-C20 alkyl or alkenyl. X- is as defined above.
[0038] The iodine value of the quaternary ammonium fabric conditioning material is preferably 0-80, more preferably 0-60, and most preferably 0-45. The iodine value can be appropriately selected. Substantially saturated materials having an iodine value of 0-5, preferably 0-1, can be used in the compositions described herein. Such materials are referred to as "hardened" quaternary ammonium compounds.
[0039] Another preferred range of the iodine value is 20-60, preferably 25-50, more preferably 30-45. This type of material is a "soft" triethanolamine quaternary ammonium compound, preferably triethanolamine dialkyl ester methyl sulfate. Such ester-linked triethanolamine quaternary ammonium compounds contain unsaturated fatty chains.
[0040] If a mixture of quaternary ammonium materials is present in the composition, the above iodine value represents the average iodine value of the parent fatty acyl compounds or fatty acids of all the quaternary ammonium materials present. Similarly, if any saturated quaternary ammonium materials are present in the composition, the iodine value represents the average iodine value of the fatty acid parent acyl compounds of all the quaternary ammonium materials present.
[0041] In the context of the compositions described herein, the iodine value refers to the iodine value of the fatty acids used to produce the QAC, which is determined by NMR spectroscopy to measure the degree of unsaturation present in the material, as described by Johnson and Shoolery in Anal. Chem., 34, 1136 (1962).
[0042] Another type of quaternary ammonium compound can be a non-ester quaternary ammonium material represented by formula (VI):
[0043]
[0044] where each R 1 group is independently selected from C1 to C4 alkyl, hydroxyalkyl or C2 to C4 alkenyl; R 2 group is independently selected from C8 to C28 alkyl or alkenyl, and X- is as defined above.
[0045] In a preferred embodiment, the fabric softening active comprises a mixture of a cationic quaternary ammonium compound having more than one long carbon chain and a second surfactant selected from single-chain cationic surfactants and / or non-ionic surfactants. Preferably, the cationic quaternary ammonium compound having more than one long carbon chain and the second surfactant are present in a ratio of 1:10 - 10:1, more preferably 1:5 to 5:1. The combination of the cationic quaternary ammonium compound having more than one long carbon chain and the second surfactant selected from single-chain cationic surfactants and / or non-ionic surfactants provides a solid composition which can be diluted with water to form a stable liquid fabric softener and provides excellent softening. The cationic quaternary ammonium compound having more than one long carbon chain is as described above.
[0046] Suitable single-chain cationic surfactants preferably have the following general formula:
[0047] (R1)3-N + -R2X -
[0048] where each R1 independently contains 1 to 6 carbon atoms and is selected from alkyl, alkenyl, aryl or combinations thereof. Each R1 can independently contain a hydroxyl group. Preferably, at least two of the R1 groups correspond to methyl.
[0049] where R2 contains at least 10 carbon atoms. The carbon atoms can be in the form of alkyl, alkenyl, aryl or combinations thereof. Preferably, the single-chain cationic surfactant contains at least 12 carbon atoms, preferably at least 14, most preferably at least 16. R2 can further contain other functional groups, such as ester groups or hydroxyl groups. X- is an anionic counterion, such as a halide ion or an alkyl sulfate, such as chloride ion or methyl sulfate.
[0050] Preferred cationic surfactants include hydroxyethyl lauryldimethyl ammonium chloride, cetyl trimethyl ammonium chloride (CTAC), behenyl trimethyl ammonium chloride (BTAC), alkyldimethyl hydroxyethyl ammonium chloride, such as Praepagen HY, which is derived from Clariant GmbH.
[0051] The compositions described herein comprise greater than 5 wt% of a fabric softening active, more preferably greater than 10 wt% of a fabric softening active, and most preferably greater than 20 wt% of a fabric softening active, based on the weight of the composition. The fabric conditioners described herein comprise less than 80 wt% of a fabric softening active, more preferably less than 70 wt% of a fabric softening active, and most preferably less than 65 wt% of a fabric softening active, based on the weight of the composition. The fabric conditioner comprises 5 - 80 wt% of a fabric softening active, preferably 10 - 70 wt% of a fabric softening active, more preferably 20 - 65 wt% of a fabric softening active, based on the weight of the composition.
[0052] Carbonaceous material
[0053] The compositions described herein comprise a carbonaceous material. The carbonaceous material results in an increase in the strength of the solid composition. A carbonaceous material refers to a material having a 2D carbon lattice nanostructure. The 2D lattice can be flat, such as graphene, or can be shaped into a 3D shape, such as a carbon nanotube. The carbonaceous material can be part of a larger structure, such as a composite material, such as a clay-carbonaceous material composite. Preferably, the carbonaceous material comprises a material selected from carbon nanotubes, graphene, activated carbon, and combinations thereof. More preferably, the carbonaceous material preferably comprises graphene and / or its derivatives, and most preferably comprises graphene oxide.
[0054] Graphene is an allotrope formed by a single layer of carbon atoms arranged in a hexagonal lattice structure. Graphene can be obtained in two ways. The first is by exfoliating layers from graphite until a graphene monolayer is obtained. The second is called chemical vapor deposition (CVD), and in which large-scale uniformity can be obtained and controlled.
[0055] Preferably, the graphene derivative suitable for the compositions described herein is graphene oxide. Graphene oxide can be manufactured by the Hummer method. Graphene oxide is also commercially available and can be obtained from suppliers such as Platonic Nanotech.
[0056] The compositions described herein preferably comprise 0.001 - 2 wt% of a carbonaceous material, more preferably 0.0025 - 1 wt% of a carbonaceous material, even more preferably 0.005 - 0.5 wt% of a carbonaceous material, and most preferably 0.01 - 0.25 wt% of a carbonaceous material.
[0057] Water-soluble carrier
[0058] The compositions described herein comprise a water-soluble carrier. The water-soluble carrier provides a solid structure for the solid fabric conditioner. The composition may comprise one carrier material or a combination of different carrier materials.
[0059] Suitable water-soluble carrier materials may be selected from the group consisting of: synthetic polymers (e.g., polyethylene glycol, ethylene oxide / propylene oxide block copolymers, polyvinyl alcohol, polyvinyl acetate and its derivatives), proteins (e.g., gelatin, albumin, casein), saccharides (e.g., dextrose, fructose, galactose, glucose, isoglucose, sucrose), polysaccharides (e.g., starch, xanthan gum, cellulose or its derivatives), vegetable soaps (e.g., coconut soap beads or palm soap), ethoxylated nonionic surfactants (having the formula R1O(R2O)xH, where R1 preferably contains 12 to 20 carbon atoms, R2 is a mixture of C2H4 or C2H4 and C3H6 units, and x = 8 to 120), urea and combinations thereof. Preferably synthetic polymers (e.g., polyethylene glycol, ethylene oxide / propylene oxide block copolymers, polyvinyl alcohol, polyvinyl acetate and its derivatives), proteins (e.g., gelatin, albumin, casein), polysaccharides (e.g., starch, xanthan gum, cellulose or its derivatives), vegetable soaps (e.g., coconut soap beads or palm soap), ethoxylated nonionic surfactants (having the formula R1O(R2O)xH, where R1 preferably contains 12 to 20 carbon atoms, R2 is a mixture of C2H4 or C2H4 and C3H6 units and x = 8 to 120) and combinations thereof.
[0060] Examples of suitable carrier materials include: water-soluble organic alkali metal salts, water-soluble inorganic alkaline earth metal salts, water-soluble organic alkaline earth metal salts, water-soluble carbohydrates, water-soluble silicates, water-soluble urea, starch, xanthan gum, dextrose, clay, water-insoluble silicates, carboxymethyl cellulose citrate, fatty acids, fatty alcohols, diglycerides of hydrogenated tallow, glycerol, polyvinyl alcohol, nonionic surfactants purchased from BASF under the trade name Lutensol, and combinations thereof.
[0061] More preferably, the water-soluble carrier is selected from polysaccharides, more preferably cellulose derivatives. Most preferably, it is a cellulose ether derivative. Generally, cellulose ether derivatives are obtained by substituting one or more hydrogen atoms of the hydroxyl groups in the anhydroglucose units of cellulose with alkyl or substituted alkyl groups. The degree of substitution (DS) is one of the factors defining the properties of cellulose ether derivatives, particularly solubility in water. It is defined as the number of substituted hydroxyl groups per glucose molecule between 0 and 3. For example, cellulose ether derivatives with a degree of substitution of 1.2 to 2.4 are soluble in cold water. Examples of cellulose ether derivatives suitable for the compositions described herein include methylcellulose (MC), hydroxyethylcellulose (HEC), hydroxypropylcellulose (HPC), hydroxypropylmethylcellulose (HPMC), carboxymethylcellulose (CMC), and sodium carboxymethylcellulose (SCMC).
[0062] Preferably, the cellulose ether derivative is selected from hydroxypropylmethylcellulose, methylcellulose, hydroxypropylcellulose, and combinations thereof. The most preferred cellulose ether derivative is hydroxypropylmethylcellulose.
[0063] The compositions described herein preferably comprise from 2 to 80% by weight, preferably from 5 to 70% by weight, more preferably from 7.5 to 50% by weight, and most preferably from 10 to 40% by weight of the water-soluble carrier material, based on the weight of the composition.
[0064] The water-soluble carrier preferably has a solubility of at least 0.5% by weight in distilled water at 25 °C. Preferably, the solubility in distilled water at 25 °C is at least 1.0% by weight, more preferably at least 2% by weight, and most preferably at least 3% by weight. In other words, the solubility is at least 5 mg / ml distilled water at 25 °C, preferably at least 10 mg / ml distilled water at 25 °C, more preferably at least 20 mg / ml distilled water at 25 °C, and most preferably 30 mg / ml distilled water at 25 °C.
[0065] Swelling and disintegrating agent
[0066] The compositions described herein preferably comprise a swelling and disintegrating agent. A swelling and disintegrating agent herein refers to a component that swells upon contact with water. The swelling and disintegrating agent acts in synergy with the carbonaceous material to provide improved strength.
[0067] Preferably, the water absorption ratio (WAR) of the swelling and disintegrating agent is greater than 1, more preferably greater than 1.5. The water absorption ratio (WAR) is a measure of how much water a material absorbs under controlled and defined conditions. The water absorption ratio is expressed as the percentage increase in the weight of the specimen:
[0068] % weight increase = [(wet weight - conditioned weight) / conditioned weight] x 100
[0069] The method described in ASTM D570 is applicable for measuring the water absorption ratio.
[0070] Specifically, the water absorption rate can be measured by the following steps:
[0071] - Produce a dry sample of the material to be tested;
[0072] - Then weigh the sample to be tested, place it in a container of boiling distilled water for 120 minutes, and then completely immerse it;
[0073] - Take out the sample and remove the remaining water with filter paper;
[0074] - Weigh the sample immediately (wet weight);
[0075] - Dry the sample at 105 °C for 20 minutes;
[0076] - Reweigh the sample (conditioned weight).
[0077] The swellable disintegrants are preferably selected from sodium carboxymethylcellulose crosslinked, sodium starch glycolate, crospovidone, C-TAG (co-ground agar), and C-TGG (co-ground guar gum), mucilage (such as from Isapgula or Fenugreek seeds), chitin, crosslinked cellulose (such as microcrystalline cellulose), sodium starch glycolate, and mixtures thereof. More preferably, the swellable disintegrants are selected from crosslinked cellulose (preferably microcrystalline cellulose), sodium starch glycolate, and mixtures thereof. Even more preferably, the water-swellable disintegrants are selected from crosslinked cellulose, and most preferably, the water-swellable disintegrants are selected from microcrystalline cellulose.
[0078] The composition may comprise from 1 to 30% by weight of a swellable disintegrant, more preferably from 2 to 20% by weight, and most preferably from 3 to 15% by weight of a swellable disintegrant.
[0079] The compositions described herein may also comprise non-swellable disintegrants. The non-swellable disintegrants herein refer to disintegrants having a water absorption rate (WAR) of less than 1. Preferably, the non-swellable disintegrants are selected from polyvinylpyrrolidone, calcium silicate, starch, magnesium stearate, and mixtures thereof.
[0080] Other ingredients
[0081] The compositions described herein may contain additional ingredients common in the field of solid fabric conditioners, such as fragrances, fragrance microcapsules, dyes, defoamers, insect repellents, shading or hueing dyes, preservatives (such as fungicides), pH buffers, fragrance carriers, hydrotropes, anti-redeposition agents, detergents, polyelectrolytes, anti-shrinkage agents, anti-wrinkle agents, antioxidants, colorants, sunscreens, anti-corrosion agents, drape aids, antistatic agents, polyvalent chelating agents, and ironing aids. The compositions described herein may contain pearlescent agents and / or opacifying agents.
[0082] Preferably, the composition contains a fragrance, more preferably 0.1 - 25% by weight of the fragrance, even more preferably 1 - 20% by weight of the fragrance, and most preferably 2 - 15% by weight of the fragrance.
[0083] Water
[0084] The solid fabric conditioners described herein are preferably "water-free" when manufactured, however they may absorb moisture during storage. Thus, preferably the composition contains 0 - 20% by weight, more preferably 0 - 15% by weight, and most preferably 0 - 12% by weight of water. The water content can be measured by thermogravimetry, such as moisture balance.
[0085] Methods for preparing and using the compositions
[0086] The solid fabric conditioner compositions described herein can be in any suitable form. A single dose of the composition can be a single article (such as a tablet or sheet), a part of a single article (i.e., a part of a sheet separated by tearing off a portion from a larger sheet), or can consist of multiple articles (such as multiple granules of the composition). Preferably, the solid composition is in the form of an article having a minimum linear dimension greater than 1 mm in any direction. The solid fabric conditioner compositions do not include powders. Preferably, the solid composition is in a form suitable for use as a single article such as a tablet or sheet. These can be referred to as 'unit doses'.
[0087] The solid fabric conditioner can be prepared by any suitable method. Preferred methods include the following steps:
[0088] a) Prepare a premix of a water-soluble carrier and water;
[0089] b) Add the fabric softening active, the carbonaceous material, and any remaining ingredients to the premix;
[0090] c) Cast the mixture onto a surface or into a mold; and
[0091] d) Remove the water, preferably by evaporation.
[0092] Step a) preferably includes mixing and / or heating.
[0093] Step b) preferably comprises mixing the fabric softening active, the carbonaceous material and any remaining ingredients with water before addition to the premix.
[0094] In step c), if casting is used, it is preferred to use an applicator to control the thickness. The mixture is preferably cast onto a polytetrafluoroethylene (PTFE) surface, such as a PTFE sheet, a PTFE-coated foil or a PTFE-coated fabric.
[0095] Step d) is preferably carried out at a temperature above room temperature (above 25 °C), preferably below 100 °C, more preferably at a temperature below 95 °C. Most preferably, water is removed at a temperature of 70 - 90 °C. Water is preferably removed to achieve a water content of the composition of 0 - 20 wt%, more preferably 0 - 15 wt%, more preferably 0 - 10 wt%, even more preferably 0 - 5 wt%, and most preferably 0 - 2 wt%.
[0096] More specifically, a homogeneous premix of water and a water-soluble carrier is prepared by mixing. Subsequently, the swellable disintegrant, the carbonaceous material, the fabric softening active and all remaining ingredients are mixed with water under high shear and then added to the premix. Thereon, the premix is cast as a sheet or film of a certain thickness onto the surface. Detailed Description
[0097] Examples
[0098] Table 1: Example Formulations
[0099]
[0100] Quaternary ammonium compound 1 -TEA palm quaternary ammonium compound
[0101] Microcrystalline cellulose 2 -KEVICEL PH102, sourced from Keval Exports
[0102] The formulation is prepared by dispersing hydroxypropyl methylcellulose in hot water to prepare a 10% polymer solution. Separately, the quaternary ammonium compound and the fragrance are mixed under high shear in the remaining water to prepare an emulsion. The remaining ingredients are added to the emulsion and mixed. The final mixture is added to the polymer solution at room temperature and mixed well under high shear until a stable foam is formed. The foam is cast onto a smooth hard surface and dried at 80 - 90 °C for 2 hours. The dried sheet is separated from the substrate upon cooling.
[0103] The tensile strength was measured using a Zeus Ultimo tensile testing machine sourced from Presto. The measurement was conducted in accordance with ASTM D882. A 2.5 cm X 5 cm sample of the sheet prepared as above was fixed to the tensile testing machine and a fixture connected to a load cell. The sheet was pulled apart at a fixed speed of 300 mm / min. The tensile strength at the breaking point of the sample was measured.
[0104] Table 2: Results
[0105] Formulation A B 1 2 Tensile strength (KgF / inch) 0.7 0.75 1.1 1.5
[0106] The tensile strength was improved by including a carbonaceous material. The improvement in tensile strength was greater when the carbonaceous material was present. This effect was further improved by the presence of a swellable disintegrant (microcrystalline cellulose).
Claims
1. A solid fabric conditioning composition comprising: a 5 - 80% by weight of a fabric softening active comprising a quaternary ammonium compound; b a carbonaceous material; and c a water-soluble carrier; wherein the carbonaceous material has a 2D carbon lattice nanostructure.
2. The solid fabric conditioning composition according to claim 1, wherein the composition further comprises a swellable disintegrant selected from the group consisting of sodium carboxymethylcellulose crosslinked, sodium carboxymethyl starch, crospovidone, C-TAG (co-ground agar), C-TGG (co-ground guar gum), mucilage (e.g., from Isapgula or Fenugreek seeds), chitin, crosslinked cellulose (e.g., microcrystalline cellulose), sodium starch glycolate, and mixtures thereof.
3. The solid fabric conditioning composition according to claim 2, wherein the swellable disintegrant is selected from disintegrants having a water absorption ratio (WAR) greater than 1.
4. The solid fabric conditioning composition according to claim 2 or 3, wherein the composition comprises 1 - 30% by weight of the swellable disintegrant.
5. The solid fabric conditioning composition according to any one of the preceding claims, wherein the fabric softening active comprises a mixture of a cationic quaternary ammonium compound having more than one long carbon chain and a second surfactant selected from single-chain cationic surfactants and / or nonionic surfactants.
6. The solid fabric conditioning composition according to any one of the preceding claims, wherein the carbonaceous material comprises a material selected from carbon nanotubes, graphene and its derivatives, activated carbon, and combinations thereof.
7. The solid fabric conditioning composition according to any one of the preceding claims, wherein the carbonaceous material comprises graphene and / or its derivatives.
8. The solid fabric conditioning composition according to any one of the preceding claims, wherein the composition comprises 0.001 - 2% by weight of the carbonaceous material.
9. The solid fabric conditioning composition according to any one of the preceding claims, wherein the water-soluble carrier is selected from: synthetic polymers, proteins, saccharides, polysaccharides, plant soaps, ethoxylated nonionic surfactants, urea, and combinations thereof.
10. The solid fabric conditioning composition according to any one of the preceding claims, wherein the water-soluble carrier is selected from: cellulose derivatives and combinations thereof.
11. The solid fabric conditioning composition according to any one of the preceding claims, wherein the composition comprises 2 - 80% by weight of the water-soluble carrier.
12. The solid fabric conditioning composition according to any one of the preceding claims, wherein the composition further comprises a fragrance.
13. A method for preparing a solid fabric conditioning composition, comprising the steps of: a preparing a premix of the water-soluble carrier and water; b adding the fabric softening active, the carbonaceous material, and any remaining ingredients to the premix; c casting the resulting mixture onto a surface or into a mold; and d removing the water, preferably by evaporation.
Citation Information
Patent Citations
Fabric treatment materials
US4137180A